The Effects of Vitamin D Supplementation on Signaling Pathway of Inflammation and Oxidative Stress in Diabetic Hemodialysis: A Randomized, Double-Blind, Placebo-Controlled Trial - Hamed Haddad Kashani; Elahe Seyed Hosseini; Hossein Nikzad; Alireza Soleimani; Maryam Soleimani; Mohammad Reza Tamadon; Fariba Keneshlou; Zatollah Asemi (Frontiers Media S.A., 2018)
Objective: This study was carried out to determine the effects of vitamin D supplementation on signaling pathway of inflammation and oxidative stress in diabetic hemodialysis (HD) patients.Methods: This randomized double-blind placebo-controlled clinical trial was conducted among 60 diabetic HD patients. Subjects were randomly allocated into two groups to intake either vitamin D supplements at a dosage of 50,000 IU (n = 30) or placebo (n = 30) every 2 weeks for 12 weeks. Gene expression of inflammatory cytokines and biomarkers of oxidative stress were assessed in peripheral blood mononuclear cells (PBMCs) of diabetic HD patients with RT-PCR method.Results: Results of RT-PCR indicated that after the 12-week intervention, compared to the placebo, vitamin D supplementation downregulated gene expression of interleukin (IL)-1β (P = 0.02), tumor necrosis factor alpha (TNF-α) (P = 0.02) and interferon gamma (IFN-γ) (P = 0.03) in PBMCs of diabetic HD patients. Additionally, vitamin D supplementation, compared to the placebo, downregulated gene expression of transforming growth factor beta (TGF-β) (P = 0.04), protein kinase C (PKC) (P = 0.001), and mitogen-activated protein kinases 1 (MAPK1) (P = 0.02) in PBMCs of diabetic HD patients. Although not significant, vitamin D supplementation let to a reduction of nuclear factor kappa B (NF-kB) (p = 0.75) expression in PBMCs isolated from diabetic patients compared to the placebo group. There was no statistically significant change following supplementation with vitamin D on gene expression of interleukin (IL)-4, IL-6, and vascular endothelial growth factor (VEGF) in PBMCs of diabetic HD patients.Conclusions: Overall, we found that vitamin D supplementation for 12 weeks among diabetic HD patients had beneficial effects on few gene expression related to inflammation and oxidative stress.Clinical trial registration: IRCT201701035623N101. Registered on January 8, 2017.